Influence of particle size-shape correlation on the shear strength of scaled samples of coarse mine waste - Linero, S; Fityus, S; Simmons, JV; Azéma, E; Estrada, N; Dixon, J (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Coarse materials like rockfill and coarse mine waste must be scalped or scaled for shear strength testing in the laboratory as the size of commercial equipment is not big enough to test the full-scale material. Samples of coarse material prepared for testing differ from their prototypes in the characteristic sizes of the particles and/or the form of the particle size distribution (PSD) curve. The representativeness of the shear strength parameter determined in the laboratory on scaled samples is questionable, nevertheless they are typically used for geotechnical design without additional consideration. The particle shapes in a natural mine waste of colluvium sediments derived from eroded ancient sedimentary rocks from the Pilbara region of Australia was analysed and a correlation between shape and size was identified. The fragments have a particle shape ranging from slabs to sub-equant blocks with a tendency of larger particles to be flatter and platy. Therefore, material scaling for shear strength determinations inevitably alters not only the size of particles and proportion of sizes, but also the characteristic shapes of the material particles as it implies substituting larger (slabs) particles by smaller (sub-equant) particles. The direct-shear shear strength of a prototype sample of the colluvium sediment was evaluated in the laboratory, as well as two different scaled representations (models) with reduced maximum particle size. The scaled specimens, composed of more equant fragments due to the nature of the size-shape correlation, showed lower shear strength compared with the prototype sample. Simulations with a discrete element method reveal that the changes in the shear strength observed when altering the PSD are not due to the change in particle sizes. Instead, these changes in shear strength result from the variation of the particle shapes induced by the alteration of the PSD. This suggests that particle shape is a higher order factor than particle sizes and PSD shape on the shear strength of granular materials. This finding highlights the importance of particle shape quantification in soil classification and its consideration in activities such as sampling, sub-sampling, and scaling of coarse materials for geotechnical testing.
Keywords: material scaling